Sentinel-2 Data set for Uganda - Ardö, Jonas (Lund University, 2021)
Optical top of the atmosphere reflectance data from the Earth resource satellite Sentinel-2 for Uganda (2018-2020) was downloaded and processed in a systematic way to bottom of the atmosphere reflectance with the open software FORCE (Framework for Operational Radiometric Correction for Environmental monitoring, see https://force-eo.readthedocs.io/en/latest/). For each year (2018-2020), the number of clear sky observations were calculated and a best available pixel mosaic were created. For each quarter (12 in total), for two vegetation indices (EVI = Enhanced Vegetation Index and NDVI = Normalized Difference Vegetation Index) a number of relevant measures were calculated (minimum, maximum, mean, standard deviation, 5%, 50% (median) and 95% quantiles). The data have 10-meter spatial resolution and are stored in GeoTIFF format.
Data are suitable for studies of vegetation and vegetation changes. More information and details in article published in Data (https://www.mdpi.com/journal/data), 'submitted' 2021-02-15

Optiska ’top of the atmosphere’ reflektans data från jordresurssatelliten Sentinel-2 för Uganda (2018-2020) laddades ner och processerades på ett systematiskt sätt till ’ bottom of the atmosphere’ reflektans med den öppna mjukvaran FORCE (Framework for Operational Radiometric Correction for Environmental monitoring, se https://force-eo.readthedocs.io/en/latest/). För varje år (2018-2020) beräknades antalet molnfria observationer och en bäst tillgänglig pixel mosaik skapades. För varje kvartal (12 totalt) beräknades för två vegetations index (EVI = Enhanced Vegetation Index och NDVI= Normalized Difference Vegetation Index) ett antal relevanta mått (minimum, maximum, medelvärde,standard avvikelse, 5%-, 50%- (median) och 95%-kvantiler). Data har 10 meters rumslig upplösning och är i GeoTIFF format.
Data är lämpliga för studier av framförallt vegetation och vegetationsförändringar. Mer information och detaljer i artikel publicerad i Data (https://www.mdpi.com/journal/data), 'submitted' 2021-02-15
Sentinel-2 data för Uganda
Keywords: LAND SURFACE; REFLECTANCE; passive remote sensing system; remote sensing data; Earth observation data; Jordobservationsdata; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Physical Geography; Naturgeografi; Imagery / Base Maps / Earth Cover; Arealtäckande bilder och bakgrundskartor